Trimetazidine stimulates intracellular Ca2+ transients and zebrafish locomotor activity in spinal neurons - Sara Bernardi; Sara Vitolo; Chiara Gabellini; Maria Marchese; Elisabetta Ferraro (Scientific Reports)
Abstract The metabolic modulator trimetazidine (TMZ) is an antianginal recently found to improve skeletal muscle performance in mice models of sarcopenia and of amyotrophic lateral sclerosis (ALS). The mechanism underlying the effect of TMZ on locomotor activity has been proposed to rely on its ability to enhance metabolic efficiency with a consequent improvement of myogenesis and of neuromuscular junction (NMJ) and muscle function. However, although promising and therefore under clinical trials, the mechanism of action of TMZ has not been clearly disclosed; here we hypothesized that it might involve the modulation of neuronal Ca2+ flows. We studied the effect of TMZ on Ca2+ dynamics in vivo, by using the transgenic zebrafish line Tg(neurod1:GCaMP6f) in which the neuronal expression of the Ca2+ indicator GCaMP allows to visualize Ca2+ dynamics in neurons of zebrafish larvae. By this elegant tool, we demonstrated, for the first time, that TMZ promotes an increase of intracellular Ca2+ transients in zebrafish spinal neurons likely enhancing motor neuron firing, which correlates with enhanced motor performance induced by this drug. Even though elevated intracellular Ca2+ levels have often been associated to neurotoxicity, it is unclear if the neuronal excitability features in some neuro-muscular disorders are compensatory or pathological. Therefore, this newly reported effect of TMZ which transiently and selectively enhances spinal neuron firing deserves to be further detailed and taken into account when the possible repurposing of this drug is proposed for the treatment of neuro-muscular disorders.